Pelatihan Perawatan Tubuh Sebagai Upaya Pemberdayaan dan Keterampilan Massage Lulur Bagi Penerima Manfaat di Panti Pelayanan Sosial PGOT Mardi Utomo - Nurulisma Saputri; Kuswidyaningrum NJ (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
This community service is a form of collaboration between the PGOT Mardi Utomo Social Service Center and AKS  Ibu Kartini Semarang. Implementation of Vocational or skills guidance program activities as an effort to empower the potential of human resources in the Mardi Utomo social service center (PPS) beggars homeless and displaced people (PGOT) in order to build social functioning of community life for beneficiaries towards independence in the field of Body Care. The purpose of this activity is to provide recipients with knowledge and skills in body care massage or body massage and body scrub as an empowerment effort for beneficiaries to provide knowledge of the ability to massage the body and body scrub so that it becomes an income opportunity by opening a massage and body scrub service business. The learning and mentoring process for beneficiaries was carried out for 5 months using the lecture method, direct demonstration as well as alternating practice. 10 beneficiary participants participated in the training from the delivery of material, demonstrations to practicing body care massage / traditional massage and scrubs. The results of community service activities run smoothly according to the activity schedule and achieve the objectives of this activity to create beneficiaries who have skills. In accordance with the PGOT Mardi Utomo social institution activity program, the implementation of vocational guidance or skills as an effort to empower beneficiaries. Evaluation of implementation